Voyage du sieur Paul Lucas, fait par ordre du roy dans la Grece, l'Asie Mineure, la Macedoine et l'Afrique - Lucas, Paul, 1664-1737. (A Paris)
2 cilt (1. c. [28], 410 sayfa ; 2. c. [8], 417, [3] sayfa)